Avanzando en la práctica del codesarrollo. Dos experiencias formativas - Carballo de la Riva, Marta; Puerto, Luis Miguel (Revista Española de Desarrollo y Cooperación, 2023)
The following article is an aproach to waht is oficially called co-development, focusing in a formative action, a Co-Development program, directed to latin-american migrants. The abovementioned action is framed by the proposals of Greco Plan in it’s 1.4 point and, specifically “Education of migrants that could be an agent of development on their return to their countries”. As a new idea it could be considered interesting the disconection between education and return, looking at the concept co-development from diferent parameters than those included in the Plan so far.